Comparison of Students’ Attitudes in Science Subjects In Urban And Rural Areas - Astalini Astalini; Dwi Agus Kurniawan; Darmaji Darmaji; Lika Anggraini (Journal of Educational Science and Technology (EST), 2020)
This study aims to determine differences in attitudes held by students who are in rural and urban areas. Because attitude is the most important thing in 21st century education. The methodology in this study uses quantitative research with a survey design that uses a total sample of 2815 students based on total sampling collection techniques. In this study, using the ANOVA test with Poshoc further tests to determine differences in attitudes held by students. The results of this study found differences in attitudes held by students in rural areas and students in urban areas, that there were significant differences held by students in science subjects. Therefore, by knowing the differences that are owned by urban and rural students can be used as a benchmark by the government to develop education that can also focus on students' affective, not just cognitive so that teachers can also apply appropriate learning methods aimed at making students able to have a good attitude that will help themselves both in school and in the community.